Evaluation of the temperature and humidity index to support the implementation of a rearing system for ruminants in the Western Amazon - Silva, Welligton Conceição da; Printes, Oscar Vitor Nina; Lima, Dagmar Oliveira; Silva, Éder Bruno Rebelo da; dos Santos, Maria Roseane Pereira; Camargo Júnior, Raimundo Nonato Colares; Barbosa, Antônio Vinicius Corrêa; Silva, Jamile Andréa Rodrigues da; Silva, André Guimarães Maciel e; Silva, Lilian Kátia Ximenes; Araújo, Cláudio Vieira de; Britto, Elton Nunes; et al. (Frontiers in Veterinary Science, 2023)
The good productive and reproductive performance of the animals depends on multiple factors, among which are the favorable climatic conditions, which are responsible for causing changes in the physiological and behavioral responses of the animals reared in different systems. Thus, the objective of this study was to evaluate the Temperature and Humidity Index (THI) to support the implementation of a rearing system in ruminants in the Western Amazon, Brazil. Data were collected through the Meteorological Database for Teaching and Research (BDMEP), obtaining data on average monthly temperature and relative humidity, referring to the capitals of Manaus (Amazonas), Boa Vista (Roraima) and Rio Branco (Acre), in the period from 1993 to 2020, referring to the months of January to December. The temperature and humidity index (THI) was calculated. The RStudio Version 1.3.1093 software with the ExpDes.pt library was used with a completely random design at 5% significance. It is possible to observe significant climatic variations during the months as well as the years of study, with the animals under thermal stress with THI greater than 72 or in a warning signal, with a gradual increase in temperature and humidity indices in the last 10 years.